Survey of Bitcoin de-anonymization technology - CHENG Jie; JIN Wei; XIA Qing; LI Miao; DAI Wei; ZHANG Yafeng; DAI Peng; LI Yucheng (Tongxin xuebao)
The Bitcoin system, based on blockchain technology, features decentralization, borderlessness, and anonymity, drawing widespread attention from academia and industry. While providing privacy protection for users, the Bitcoin system also facilitates illegal activities. Consequently, de-anonymization techniques have been actively researched, yielding a series of research results. Existing surveys primarily focus on privacy protection schemes, lacking a systematic analysis of de-anonymization techniques. The existing de-anonymization techniques and their effectiveness were analyzed from three dimensions, user identity identification, associated address recognition, and asset flow tracing. The current development status and challenges are summarized, and future research directions are pointed out.